Public service social media priming towards gaining the trust of youths / Nur Risyah Musa and Mokhtar Muhammad - Musa, Nur Risyah; Muhammad, Mokhtar (Centre for Media and Information Warfare Studies, Faculty of Communication and Media Studies, Universiti Teknologi Mara, Malaysia, 2019)
Social media has vastly proliferated and become a vital platform for political parties, businesses and consumers to disseminate their organisation's interests and agenda. The public service of Malaysia too has benefited from social media as a strategic communication medium in disseminating government policies and building a relationship with main stakeholders namely the public it represents. Youths as dynamic assets to communities, leverage on social media as a powerful communication tool to transmit their ideas and opinions to a large audience. However, despite the engagement and communication between the government and youth in social media, the government failed to garner the trust of youths due to the difference of communication wavelengths and understanding which results in disinterest and disinvolvement of youths towards government's communication content. Youths are forced to look for new ways to obtain information and shy away from engaging in government social media. Therefore, this study aims to justify that the adoption of social media priming helps the public service of Malaysia to improve its social media communication towards gaining the trust of youths. The study analyses and identifies the use of keywords, symbolic representations and the types of content being communicated by the public service that indicates the approach used in gaining youths' trust. This study applies a thematic qualitative textual analysis that can be best used to interpret and analyse the unique and latent meaning embedded within the texts posted by KBSMalaysia Facebook page, a public service representative sample. The finding shows that words that are the most direct, simple and attractive can have the most profound impact. The study also points out that the public service is seen as lagging in their usage of input seeking, where it does not focus greatly on two-way communication engagement. Therefore, this study provides a better understanding of conducting the right social media priming approach through the use of meaningful words. With genuine content and connections in social media, the public service can achieve its desired policy objectives to be better communicated with the public in a valuable way and have a long-term approach and relationship which will increase the public's trust not only in the aspect of accountability and credibility of the public service but also to the service delivery rendered by them.